The Role of Educational Games Based on Local Wisdom in Improving Reading Literacy in Elementary Schools - Indriani, Inditha Jauhari; Muqarramah, Khairial; Nurhayani , Maqfirah Sri (Education : Jurnal Sosial Humaniora dan Pendidikan, 2025)
The low level of reading literacy among elementary school students remains a tangible challenge in the field of education, particularly when learning has yet to fully engage with cultural contexts familiar to students' everyday lives. This study aims to explore the effectiveness of educational games based on local wisdom as a learning medium capable of meaningfully improving reading literacy skills. Employing a mixed methods approach, this research combines quantitative analysis through pre-tests and post-tests on two groups (experimental and control), as well as qualitative analysis through participatory observation and semi-structured interviews. Quantitative findings indicate a significant improvement in reading literacy among the experimental group following the game-based learning intervention. Meanwhile, qualitative data reveal that students tend to be more emotionally and cognitively engaged when learning with media that incorporate local cultural elements, such as wayang stories or traditional markets. Not only does the educational game foster reading interest, but it also strengthens the connection between learning content and students’ cultural realities. This study contributes to the effort of presenting a more contextual, relevant, and motivating learning approach, particularly in the development of literacy media grounded in both technology and culture. The findings also open up opportunities for the development of more inclusive and locally-based education policies in the digital era.